2019
DOI: 10.48084/etasr.2722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Rolling and Aging Treatment on the Properties of Cu-Be Alloy

Abstract: The effects of precipitated phases during aging treatment on the properties of the Cu-Be alloy have been extensively studied. In this study, the effect of cold rolling on the precipitated phases of the Cu-Be alloy compared with non-deformed alloy during isothermal and low heating rate aging of 20C/min have been investigated. Hardness changes, differential scanning calorimetry (DSC), dilatation analysis, and transmission electron microscopy (TEM) were used in this study. Hardening and contraction were strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The effect of cold rolling on the age-hardening behavior has been reported, and it was found that the formation of γ″ and γ′ phases was accelerated by the effect of cold rolling [7]. Cold rolling also produces an increase in hardness at an early aging time.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of cold rolling on the age-hardening behavior has been reported, and it was found that the formation of γ″ and γ′ phases was accelerated by the effect of cold rolling [7]. Cold rolling also produces an increase in hardness at an early aging time.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon steels are used in a wide range of applications, such as structural components, industrial pipes, and kitchen appliances. With regard to applications in the oil and gas industry, the carbon dioxide (CO 2 ) corrosion could be considered as one of the major forms of corrosion [10][11][12][13]. In this study, we discuss carbon steel as the most employable material for the construction of gas and oil pipelines, desalination plants, and water treatment construction and equipment.…”
Section: Introductionmentioning
confidence: 99%